Optimization of Vestibular Tests in Adolescents - Davronov U. F.; Normuradov N. A.; G'ulomov A. M. (Journal of Science in Medicine and Life, 2025)
When studying the vestibular apparatus of healthy adolescents by the method of electronistagmography after a rotational test, 23 of 36 adolescents revealed secondary nystagmus. Secondary nystagmus was often observed and was more pronounced to the left. Its duration exceeded the duration of primary nystagmus, but the intensity in terms of frequency, amplitude and speed of the slow phase was much less. Secondary nystagmus was closely associated with latent spontaneous nystagmus. The latter has always been accompanied by prolonged secondary nystagmus in the same direction. Detection of prolonged unilateral secondary nystagmus should obviously have the same significance for issues of professional suitability as the detection of latent spontaneous nystagmus.